2010
DOI: 10.4081/ejh.2010.e1
|View full text |Cite
|
Sign up to set email alerts
|

Folliculostellate cells in pituitary pars distalis of male viscacha: immunohistochemical, morphometric and ultrastructural study

Abstract: Folliculostellate cells (FSC) have been reported in pituitary of several mammalian species. FSC morphology and secreted substances have been instrumental to the understanding of their function. The purpose of this work was to perform an immunohistochemical, morphometric and ultrastructural study of the pituitary pars distalis FSC in adult male viscacha and to analyze their relation with hormone secreting cells. Immunohistochemistry and image analysis were carried out in different sectors of the gland, from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In this study, significant differences in the %IA of S‐100 protein and GFAP may indicate that IC undergo seasonal variations in their biochemical properties, in relation to seasonal changes in the pinealocyte activity. It has been reported that S‐100 protein acts as a cytoskeleton dynamics regulator, intracellular signal transducer as well as paracrine regulator at extracellular level (Donato, ; Donato et al, ; Acosta et al, ). In viscachas, the higher expression during winter may reflect a major activity of IC according to pinealocyte activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, significant differences in the %IA of S‐100 protein and GFAP may indicate that IC undergo seasonal variations in their biochemical properties, in relation to seasonal changes in the pinealocyte activity. It has been reported that S‐100 protein acts as a cytoskeleton dynamics regulator, intracellular signal transducer as well as paracrine regulator at extracellular level (Donato, ; Donato et al, ; Acosta et al, ). In viscachas, the higher expression during winter may reflect a major activity of IC according to pinealocyte activity.…”
Section: Discussionmentioning
confidence: 99%
“…HK 183–5K; BioGenex, San Ramon, CA), resulting in a fuchsia precipitate. DAB and New Fuchsin were selected as chromogens to visualize the antigens, since this combination is known to provide good contrast (Acosta et al, ). The sections were counterstained with Harris′ hematoxylin for 10 sec, washed for 2 min in running water, and mounted with a permanent aqueous mounting medium (SuperMount, BioGenex San Ramon, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genex), resulting in a fuchsia precipitate. DAB and new fuchsin were selected as chromogens to visualize the antigens, since this combination is known to provide good contrast [Acosta et al, 2010;Busolini et al, 2017]. The sections were counterstained with Harris' hematoxylin for 10 s, washed for 2 min under running water, and mounted with a permanent aqueous mounting medium (SuperMount; BioGenex).…”
Section: Double Ihc For S-100 and Gfapmentioning
confidence: 99%
“…The S-100 protein is the most commonly used marker protein for the identification of glial cells in the central nervous system, especially in astrocytes, neural progenitor cells, maturing oligodendrocytes, and some types of neurons. In other cell types, such as pituitary folliculostellate cells, Langerhans cells, melanocytes, and chondrocytes, expression of the S-100 protein has also been reported [Haimoto et al, 1987;Böni et al, 1997;Rambotti et al, 1999;Acosta et al, 2010;Acosta and Mohamed, 2013]. S-100 protein is exclusively expressed in vertebrates and performs several intracellular functions, as well as some extracellular ones.…”
Section: Introductionmentioning
confidence: 99%